Efectos adversos corneales del uso de los AINES oculares (2021)
Topical ophthalmic non-steroidal anti-inflammatory drugs (NSAIDs) are a group of drugs that combine therapeutic effects and adverse effects; contributing analgesic, anti-inflammatory and antipyretic properties (1). They are formulated after surgical procedures such as keratoplasty, cataract extraction, refractive surgery, and for the control of inflammatory-type ocular surface disorders. Furthermore, his activity anti-inflammatory lies in the inhibition of the enzyme cyclooxygenase (COX) in its isoforms like COX-1 and COX-2, the first is a physiological form that is found naturally common in the kidney, intestinal tract, monocytes/macrophages and platelets. It is expressed in formation of essential prostaglandins (2). The action of NSAIDs is to generate a reversible inhibition of these enzymes in order to to slow down the formation of prostaglandins whose action is to mediate the processes inflammatory. In contrast, COX-2 is almost undetectable in normal tissues, its manifestation is given by the release of some inflammatory-type prostaglandins, which lead to the appearance of inflammatory mechanisms and the amplification of signals painful in the inflamed areas(3).